The analysis of the energy intensity of economies by selected indicators of sustainability (Rio+ 20) - Adamišin, Peter; Huttmanová, Emília (Journal of Economic Development, Environment and People, 2013)
The aim of this paper is to analyze the status and the development of energy intensity in selected countries of Central and South-eastern Europe. Reducing of energy consumption is one of the ways to ensure not only economic, but also environmental aspects of sustainability. This paper describes the relationship between economic development and energy intensity of countries, particularly the countries of the selected region.